Mekanisme Molekuler Probiotik dalam Modulasi Fungsi Barrier Usus dan Respons Imun: A Systematic Literature Review - Salam, Nurfadillah; Aufa Hudzhaifah; Racmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study reviews the molecular mechanisms of probiotics in maintaining intestinal barrier function and regulating inflammation through a Systematic Literature Review of 21 selected articles from the Scopus database (2023–2026). The findings show that probiotics strengthen intestinal barrier integrity by modulating the TLR–NF-κB–MAPK pathway, increasing tight junction protein expression, regulating mitochondrial apoptosis, and influencing SCFA metabolism, bile acids, and the Akt/mTOR pathway. Evidence from in vitro, in vivo, and multi-omics studies supports the protective role of probiotics against intestinal inflammation. Overall, probiotics demonstrate strong potential as microbiome-based therapeutic agents, although further clinical validation is still required.